Scurvy in the Intensive Care Unit - Amarah Baluch MD; David Landsberg MD (SAGE Publishing, 2021)
Scurvy, caused by vitamin C deficiency, is a forgotten disease in the modern era of medicine. The prevalence of vitamin C deficiency in the United States is reported to be 7.1%. We present a case of a 56-year-old man with a history of chronic alcohol use who was admitted to the intensive care unit due to sepsis. He was found to have a rash on his hands and feet which consisted of palpable lesions as well as petechiae. Work up of the patient's skin pathology revealed ascorbic acid deficiency, also known as scurvy. This case highlights the importance of considering severe nutritional deficiency in patients with underlying alcohol use who present with skin findings that may mimic those of a vasculitis. Although rare, vitamin C deficiency still exists, and it is important to be aware of presenting signs and identify those who are at risk.